Cord blood nucleated RBCs as a potential tool in prediction of neonatal hyperbilirubinemia in ABO incompatibility susceptible neonates - Rao, Shravya S.; Mahendrappa, Kotyal B. (International Journal of Contemporary Pediatrics, 2021)
Background: Neonatal hyperbilirubinemia is one of the most commonly encountered conditions in neonatal period. Early recognition and prompt intervention can prevent its dreadful complication like bilirubin encephalopathy. nucleated red blood cells (nRBC) are released into the peripheral circulation in conditions causing oxidative stress. This study aims at finding the relation between nRBC and neonatal hyperbilirubinemia. Methods: This hospital based prospective cohort study was conducted on 100 neonates. The neonates were divided into 2 groups: Group 1- cases (n=50) included neonates born to O positive mothers with A/B blood groups and Group 2-controls (n=50) with neonates born to O positive mothers with O blood group. The cord blood nRBC, TSB at 48 hours and requirement of phototherapy were the variables which were considered. Statistical analysis was done using SPSS 22 version software with appropriate statistical methods applied. Results: The mean cord nRBC was 7.26±2.65 (Group 1) and 3.04±0.92 (Group 2) respectively. ROC curve for cord nRBC revealed AUC 0.944 at 4.0 cut-off with sensitivity of 92%, specificity of 94%, LR+15.33 and LR-6.085 with p<0.0001. Conclusions: Cord blood nucleated RBCs is a simple, easily available test to predict the neonatal hyperbilirubinemia in ABO incompatibility susceptible neonates.